2014
DOI: 10.1111/myc.12264
|View full text |Cite
|
Sign up to set email alerts
|

Candida nivariensis in comparison to different phenotypes of Candida glabrata

Abstract: The purpose of the study was to establish the prevalence of new Candida glabrata complex species: Candida nivariensis and Candida bracarensis isolated from clinical material, evaluate their phenotypes and the prevalence of gene family encoding extracellular glycosylphosphatidylinositol-linked aspartyl proteases, crucial for C. glabrata virulence. Study material included 224 C. glabrata clinical strains. Candida glabrata phenotypes were identified using CHROMagar Candida medium. Strains were analysed by using C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
11
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(14 citation statements)
references
References 29 publications
3
11
0
Order By: Relevance
“…The expression of YPS genes significantly increases the capacity of the fungus to survive inside human macrophages ( Krysan et al 2005) . Swoboda-Kopeć et al (2014) confirmed the prevalence of three genes ( YPS2 , YPS4 , and YPS6 ) in the majority of C. glabrata strains isolated from clinical specimens. However, the prevalence of these genes in 13 clinical isolates of C. nivariensis was low ( Swoboda-Kopeć et al 2014) .…”
Section: Resultssupporting
confidence: 72%
See 3 more Smart Citations
“…The expression of YPS genes significantly increases the capacity of the fungus to survive inside human macrophages ( Krysan et al 2005) . Swoboda-Kopeć et al (2014) confirmed the prevalence of three genes ( YPS2 , YPS4 , and YPS6 ) in the majority of C. glabrata strains isolated from clinical specimens. However, the prevalence of these genes in 13 clinical isolates of C. nivariensis was low ( Swoboda-Kopeć et al 2014) .…”
Section: Resultssupporting
confidence: 72%
“… Swoboda-Kopeć et al (2014) confirmed the prevalence of three genes ( YPS2 , YPS4 , and YPS6 ) in the majority of C. glabrata strains isolated from clinical specimens. However, the prevalence of these genes in 13 clinical isolates of C. nivariensis was low ( Swoboda-Kopeć et al 2014) . Regarding the phytase activity, C. nivariensis 893391/INCA strain and C. nivariensis WM 09.150 reference strain presented a moderate production of phytase, whereas the type strain of C. glabrata exhibited a low production of this enzyme ( Table III ).…”
Section: Resultssupporting
confidence: 72%
See 2 more Smart Citations
“…The yapsins (YPS) are a family of five nonsecreted glycosylphosphatidyinositol-linked aspartic proteases that have a well-known role in cell wall integrity and increase the capacity of the fungus to survive inside human macrophages [50]. A study developed by Swoboda-Kopeć et al [51] confirmed the prevalence of three genes ( YPS2 , YPS4 , and YPS6 ) in the majority of C. glabrata strains isolated from clinical specimens.…”
Section: Discussionmentioning
confidence: 99%